A survival guide to managing employees from hell : handling idiots, whiners, slackers, and other workplace demons - Scott, Gini Graham (AMACOM, 2007)
This work draws from entertaining real-life stories to illustrate real-world solutions. It shows readers how to handle a wide range of difficult types, including: The Impossible "I"s: Incompetents, Idiots, and Imbeciles - clueless employees who simply don't know what they're doing, I've Got a Problem - employees whose work is compromised by any of a range of personal demons, from drug and alcohol problems to emotional issues, The Party-Time Performer - the employee who, although great with people, constantly turns work-time into fun-time.